HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL DENGAN PERILAKU AGRESIF REMAJA DI SMP NEGERI 278 JAKARTA - Anita Amaliah; Thrisia Febrianti; Dwi Endrasto wibowo (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
The Relationship between Emotional Intelligence and Spiritual Intelligence with Aggressive Youth Behavior in SMP Negeri 278 Jakarta. Guidance and Counseling Studies, Faculty of Teacher Training and Education, As-Syafi'iyah Islamic University. The purpose of this study was to study the relationship between emotional intelligence and spiritual intelligence with the aggressive behaviour in SMP Negeri 278 Jakarta. The method used in this research is the correlational and ex-post facto methods. The population was 201 students and samples taken using the Slovin formula were 114 students. The data collection technique used was a questionnaire. The data analysis technique used is the product moment correction technique and multiple comparison analysis. Based on the results of thought when the product with the SPSS 22.v program showed a significant relationship between emotional intelligence and adolescent intelligence with r=0.447 and Sig. 0,000 < 0.05. There was no significant relationship between spiritual intelligence and adolescent intelligence with r=0.015 and Sig. 0.473 > 0.05. There is a significant relationship between emotional intelligence and spiritual intelligence with aggressive intelligence where Fcount 14.438 <Ftable 3.08